Improving Maternal and Child Healthcare Programme Using Community-Participatory Interventions in Ebonyi State Nigeria - Chigozie Jesse Uneke; Chinwendu Ndukwe; Abel Ezeoha; Henry Urochukwu; Chinonyelum Ezeonu (Kerman University of Medical Sciences, 2014)
In Nigeria, the government is implementing the Free Maternal and Child Health Care Programme (FMCHCP). The policy is premised on the notion that financial barriers are one of the most important constraints to equitable access and use of skilled maternal and child healthcare. In Ebonyi State, Southeastern Nigeria the FMCHCP is experiencing implementation challenges including: inadequate human resource for health, inadequate funding, out of stock syndrome, inadequate infrastructure, and poor staff remuneration. Furthermore, there is less emphasis on community involvement in the programme implementation. In this policy brief, we recommend policy options that emphasize the implementation of community-based participatory interventions to strengthen the government's FMCHCP as follows: Option 1: Training community women on prenatal care, life-saving skills in case of emergency, reproductive health, care of the newborn and family planning. Option 2: Sensitizing the community women towards behavioural change, to understand what quality services that respond to their needs are but also to seek and demand for such. Option 3: Implementation packages that provide technical skills to women of childbearing age as well as mothers' groups, and traditional birth attendants for better home-based maternal and child healthcare. The effectiveness of this approach has been demonstrated in a number of community-based participatory interventions, building on the idea that if community members take part in decision-making and bring local knowledge, experiences and problems to the fore, they are more likely to own and sustain solutions to improve their communities' health.